Latviešu valodas verbu semantiskās sistēmas analīzes veids - Valdmanis, Jānis (Baltistica, 1989)
ANALYSIS OF LATVIAN VERBS AS A SEMANTIC SYSTEMThe present paper suggests the way of describing the meanings of Latvian verbs as a semantic system. Separate meanings as concrete expressions of processual indication are stated in the first step of study. The second step deals with the interrelations of meanings. Three basic points should be clarified here: the dependence of meaning upon the mode of cognition of reality; the relation of meaning to the time axis; the meaning and the identification of situation. The verb meaning totality as the expression of the qualities of the united wholeness is discussed in the third step.The author considers that such analysis gives the possibility of describing the lexical nļeanings of verbs as a semantic system of stating the logico- semantic types of verbal sentences and of constructing studies of the verb semantic systems.Making use of the notions of judgement and proposition, nine types of verbal sentences are obtained: the qualification of the subject with the one-place proposition; the qualification of the subject with the two-place proposition; the classification of the subject with the one-place proposition; the classification of the subject with the two-place proposition; the existence of the subject as a zero-place proposition; the existence of the subject as a one-place proposition; the relation of the subject in a way of a two-place proposition; the relation of the subject in a way of a three-place proposition; the relation of the subject in a way of a four-place proposition.